An Active Metamaterial Platform for Chiral Responsive Optoelectronics. (19th June 2015) - Kang, Lei; Lan, Shoufeng; Cui, Yonghao; Rodrigues, Sean P.; Liu, Yongmin; Werner, Douglas H.; Cai, Wenshan
<x xml:space="preserve">Abstract</x> Chiral‐selective non‐linear optics and optoelectronic signal generation are demonstrated in an electrically active photonic metamaterial. The metamaterial reveals significant chiroptical responses in both harmonic generation and the photon drag effect, correlated to the resonance behavior in the linear regime. The multifunctional chiral metamaterial with dual electrical and optical functionality enables transduction of chiroptical responses to electrical signals for integrated photonics.